The neuroimmune pathway of high-altitude adaptation: influence of erythrocytes on attention networks through inflammation and the autonomic nervous system - Wang, Nian-Nian; Yu, Si-Fang; Dang, Peng; Su, Rui; Li, Hao; Ma, Hai-Lin; Liu, Ming; Zhang, De-Long (Frontiers in Neuroscience, 2024)
Many studies have shown that the functional adaptation of immigrants to high-altitude is closely related to oxygen transport, inflammatory response, and autonomic nervous system. However, it remains unclear how human attention changes in response to hypoxia-induced neurophysiological activity during high-altitude exposure. In the present study, we analyzed the relationship between hypoxic-induced neurophysiological responses and attention networks in 116 immigrants (3680m) using an attention network test to simultaneously record electroencephalogram and electrocardiogram in combination with specific routine blood markers. Pathway analysis showed that red blood cells indirectly affected the three attention networks through inflammation and heart rate variability. All these observations provide experimental evidence for the existence of a neuroimmune pathway rooted in red blood cells, which represents oxygen transport capacity and is the basic physiological mechanism that determines human attention performance at high-altitude.